2022
DOI: 10.3390/cells11050860
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Acupuncture Analgesia

Abstract: Mast cells are widely distributed in various parts of the human body and play a vital role in the progression of many diseases. Recently, the close relationship between mast cells and acupoints was elucidated, and the role of mast cells in acupuncture analgesia has attracted the attention of researchers worldwide. Using mast cells, acupuncture analgesia and acupoint as key words to search CNKI, PubMed, Web of Science and other databases, combining the representative articles in these databases with the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
(90 reference statements)
1
18
0
4
Order By: Relevance
“…20 The inflammatory reactions caused by the mediators is usually related to pathological alternation of epidermal/ dermal thickness, microvasculature activity, inflammatory cell infiltration, and the clinical symptoms of skin rash, pruritus and pain. [21][22][23] As the reported pathological observation and clinical manifestation of DCS skin lesion are highly consistent with the symptom and histopathology induced by the activation of mast cells. In addition, current study has reported that 1% polidocanol injectable foam used for the treatment of varicose veins may cause mast cell-related dermatological side effects like local urticaria, which was thought to be associated with mast cells.…”
Section: Mast Cells Degranulation Process Encompasses Exocytosis and ...supporting
confidence: 80%
See 1 more Smart Citation
“…20 The inflammatory reactions caused by the mediators is usually related to pathological alternation of epidermal/ dermal thickness, microvasculature activity, inflammatory cell infiltration, and the clinical symptoms of skin rash, pruritus and pain. [21][22][23] As the reported pathological observation and clinical manifestation of DCS skin lesion are highly consistent with the symptom and histopathology induced by the activation of mast cells. In addition, current study has reported that 1% polidocanol injectable foam used for the treatment of varicose veins may cause mast cell-related dermatological side effects like local urticaria, which was thought to be associated with mast cells.…”
Section: Mast Cells Degranulation Process Encompasses Exocytosis and ...supporting
confidence: 80%
“…These granules are rich in performed mediators and synthesized de novo biological substances that directly release in the infection sites and surrounding areas 20 . The inflammatory reactions caused by the mediators is usually related to pathological alternation of epidermal/dermal thickness, microvasculature activity, inflammatory cell infiltration, and the clinical symptoms of skin rash, pruritus and pain 21–23 …”
Section: Discussionmentioning
confidence: 99%
“…The conclusion that MC stabilizers can suppress this neurological communication, provides that at least some of acupuncture’s effects are influenced by MCs activity ( 11 ). Following acupuncture, MCs moved to the local acupoints through the blood arteries of the subdermal and subcutaneous tissues, and the aggregated MCs produced more tryptase through degranulation, histamine, and 5-hydroxytryptamine (5-HT) ( 15 17 ). The nerve fibers also released more substance P and calcitonin gene-related peptide P (CGRP).…”
Section: Acupuncture Modulates Innate Immune Cells’ Activitymentioning
confidence: 99%
“…More recently, Fudan's groups have published 2 detailed reviews in English on the studies of MCs and acupuncture. 11 , 12 All of these reviews were built on the first MC hypothesis proposed by Professor Song in 1977.…”
Section: Personal Notes By the Authormentioning
confidence: 99%
“…Several leading groups of acupuncture research in China have confirmed or studied MCs' role in acupoints further and have published about this research in international scientific journals and books. These include but not limited to, Ding et al and Li et al, from Fudan University, 11 , 12 , 32 Wu et al, from the Chinese Institute of Acupuncture and Moxibustion, 33 Zhao et al, from the Chengdu University of TCM, 34 and Gong et al, from the Tianjin University of TCM. 35 …”
Section: A New Field Opened By Song's MC Theorymentioning
confidence: 99%